Diversity and Evolution of Salt Tolerance in the Genus Vigna. - Kohtaro Iseki; Yu Takahashi; Chiaki Muto; Ken Naito; Norihiko Tomooka (PLoS ONE, 2016)
Breeding salt tolerant plants is difficult without utilizing a diversity of wild crop relatives. Since the genus Vigna (family Fabaceae) is comprised of many wild relatives adapted to various environmental conditions, we evaluated the salt tolerance of 69 accessions of this genus, including that of wild and domesticated accessions originating from Asia, Africa, Oceania, and South America. We grew plants under 50 mM and 200 mM NaCl for two weeks and then measured the biomass, relative quantum yield of photosystem II, leaf Na+ concentrations, and leaf K+ concentrations. The accessions were clustered into four groups: the most tolerant, tolerant, moderately susceptible, and susceptible. From the most tolerant group, we selected six accessions, all of which were wild accessions adapted to coastal environments, as promising sources of salt tolerance because of their consistently high relative shoot biomass and relative quantum yield. Interestingly, variations in leaf Na+ concentration were observed between the accessions in the most tolerant group, suggesting different mechanisms were responsible for their salt tolerance. Phylogenetic analysis with nuclear DNA sequences revealed that salt tolerance had evolved independently at least four times in the genus Vigna, within a relatively short period. The findings suggested that simple genetic changes in a few genes might have greatly affected salt tolerances. The elucidation of genetic mechanisms of salt tolerances in the selected accessions may contribute to improving the poor salt tolerance in legume crops.